Managing the mutations: academic misconduct Australia, New Zealand, and the UK - Melanie Birks; Jane Mills; Steph Allen; Stephen Tee (International Journal for Educational Integrity, 2020)
Abstract Academic misconduct is a problem of growing concern across the tertiary education sector. While plagiarism has been the most common form of academic misconduct, the advent of software programs to detect plagiarism has seen the problem of misconduct simply mutate. As universities attempt to function in an increasingly complex environment, the factors that contribute to academic misconduct are unlikely to be easily mitigated. A multiple case study approach examined how academic misconduct is perceived in universities in in Australia, New Zealand and the United Kingdom via interviews with academics and administrators. The findings show that academic misconduct is a systemic problem that manifests in various ways and requires similarly diverse approaches to management. Greater consistency in policies and procedures, including a focus on preventative education for both staff and students, is key to managing the mutations of academic misconduct that continue to plague the higher education sector globally.